Optimisation De La Production De Pepiniere De Tomate Sous Abri A Abidjan Sud De La Côte d’Ivoire - Amidou, Ouattara; Réné, Nganzoua Kouamé; Olayossimi, Adechina (European Scientific Journal, ESJ, 2018)
This study was focused in Abidjan district, located in Laguna region of Côte d’Ivoire. The aim was to determine an innovative method of growing tomato (Lycopersicum esculentum Mill) plant nursery that involves creating optimized aerial and root zone environments. This research was carried out during two successive seasons : 2015 wet season (may to august) and 2016 dry season (january to february). The tomato variety was hybrid Lindo. The plant germination, survey characters and plant vigor at each growing season as influenced by the controlled environment agriculture were identified using a completely randomized designs with four replications. The results showed a significant variability in plant germination, height, and growth vigor. Tomato plant nursery as influenced by controlled environment agriculture create optimized aerial and root zone environments, focusing on growth benefits and limited environmental impact.